UJI FITOKIMIA, TOKSISITAS DAN AKTIVITAS ANTIBAKTERI dari EKSTRAK BERBAGAI FRAKSI DAUN MAHANG (Macarang apruinosa (Miq.) Mull. Arg.) terhadap BAKTERI Escherichia coli dan Staphylococcus aureus - Mustafidah -; Chairul Saleh; Alimuddin - (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
Phytochemical, toxicity and antibacterial activity tests of total extract, fractions of n-heksana, ethyl acetate and ethanol-water from mahang leaf (Macaranga pruinosa (M.) M. A.) from KRUS (Kebun Raya Unmul Samarinda), East Kalimantan has been carried out. Based on the secondary metabolites phytochemical test of the (Macaranga pruinosa (M.) M. A.) leaf show that total extract is contain alkaloid and steroid. n-hexane fraction is contain alkaloid and steroid. Ethyl acetate fraction is contain steroid. Ethanol-water fraction is contain alkaloid and phenolic. Brine shrimp lethality test values obtained Lethal Concentration 50 % (LC50) total extract 27,5036 ppm , n-heksana fraction 12,0773 ppm, ethyl acetate fraction 23719,2305 ppm and ethanol-water fraction 250,0384 ppm. Antibacteria activity test of extracts for Staphylococcus aureus bacteria (positive Gram) and Escherichia coli (negative Gram) minimum inhibitor consentration of 0-1 % (b/v) from extract fractions of n-heksana and fractions ethyl acetate for Staphylococcus aureus bacteria and fractions ethyl acetate for Escherichia coli bacteria.Keywords (Macaranga pruinosa (M.) M. A.), phytochemical test, Antibacteria activity test, LC 50 .